Intra-Stroke Profiling of Wheelchair Propulsion Using Inertial Measurement Units - Amy R. Lewis (Proceedings, 2018)
The instrumentation of wheelchair racing chairs is currently limited by the influence of the athlete-wheelchair system mass and performance. Inertial measurement units (IMUs) provide a lightweight solution, and have demonstrated accurate kinematic monitoring of wheelchair ball sports. With the aim of investigating the capability of IMUs detecting contact and release timings, a study was performed on seven national level wheelchair racing athletes (T34 and T54 classifications). Athletes performed treadmill-based propulsion at speeds ranging between 19 km/h and 32 km/h, with the population sample enabling comparison between classification, propulsion speed, gender, age, glove type and wheel type. Contact and release timing points of each athlete were verified against measures obtained using video capture (100 Hz), which is considered a gold standard measure. IMUs identified contact timings for all athletes, however could not consistently identify release points for all athletes. Propulsion speed and gender were found to have minimal influence on the capacity to determine contact.